2014
DOI: 10.1080/09168451.2014.915731
|View full text |Cite
|
Sign up to set email alerts
|

The hierarchic network of metal-response transcription factors in Escherichia coli

Kaneyoshi Yamamoto

Abstract: To cite this article: Kaneyoshi Yamamoto (2014) The hierarchic network of metal-response transcription factors in Escherichiacoli, Bioscience, Biotechnology, and Biochemistry, 78:5,[737][738][739][740][741][742][743][744][745][746][747]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 124 publications
(127 reference statements)
0
13
0
Order By: Relevance
“…E. coli responds to temporary low pH using the glutamate-dependent acid resistant system, which involves two complex regulatory systems: EvgAS > YdeO > GadE; and Crp> RpoS > GadX > GadW [9], [12]. In this study, we showed that YdeO directly regulates the expression of three transcription factor genes, nhaR , gadE, and gadW (see Fig.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…E. coli responds to temporary low pH using the glutamate-dependent acid resistant system, which involves two complex regulatory systems: EvgAS > YdeO > GadE; and Crp> RpoS > GadX > GadW [9], [12]. In this study, we showed that YdeO directly regulates the expression of three transcription factor genes, nhaR , gadE, and gadW (see Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Knowledge about the regulatory functions of YdeO is limited except that it is known that YdeO activates transcription of the gad system components, gadE , gadA and gadBC [7], [8], [9]. The expression of ydeO is activated by the two-component system EvgSA [9], [10], [11], forming a regulatory cascade, EvgA > YdeO > GadE [9], [12]. In this study, we performed a comprehensive interrogation of YdeO-binding sites in vivo on the E. coli genome using ChIP-chip analysis, and identified a set of YdeO-regulated genes, including four stress-response transcription factors, DctR, NhaR, GadE, and GadW, and several genes involved in respiration.…”
Section: Introductionmentioning
confidence: 99%
“…In E. coli , the promoter selectivity of RNA polymerase is determined after interaction with seven species of the sigma subunit with the promoter recognition activity (Ishihama , ). The promoter selectivity of each holoenzyme is further modulated after interaction with a total of approximately 300 species of transcription factor (TF) (Ishihama , ; Yamamoto ), of which approximately 10% are organized into the two‐component system (TCS) (Mizuno ; Yamamoto et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…In bacteria, the selection of genes for expression is mainly determined at the transcription step, by controlling the distribution of the limited number of RNA polymerase (RNAP) molecules on the genome (Ishihama, 2000(Ishihama, , 2010Yamamoto, 2014). The promoter selectivity of RNAP is determined by association with one of seven species of the sigma subunit and a total of about 300 species of transcription factor (TF) (Ishihama, 2010(Ishihama, , 2012Keseler et al, 2013;Riley et al, 2006).…”
Section: Introductionmentioning
confidence: 99%